Using Anthropometric Data and Physical Fitness Scores to Predict Selection in a National U19 Rugby Union Team - Vaz, Luis; Kraak, Wilbur; Batista, Marco; Honório, Samuel; Miguel Fernandes, Hélder (International journal of environmental research and public health, 2021)
The purpose of this study was to compare measures of anthropometry characteristics and physical fitness performance between rugby union players (17.9 ± 0.5 years old) recruited (n = 39) and non-recruited (n = 145) to the Portuguese under-19 (U19) national team, controlling for their playing position (forwards or backs). Standardized anthropometric, physical, and performance assessment tests included players’ body mass and height, push up and pull-up test, squat test, sit-and-reach test, 20 m shuttle run test, flexed arm hang test, Sargent test, handgrip strength test, Illinois agility test, and 20-m and 50-m sprint test. Results showed that recruited forwards players had better agility scores (p = 0.02, ES = −0.55) than the non-recruited forwards, whereas recruited backs players had higher right (p < 0.01, ES = 0.84) and left (p = 0.01, ES = 0.74) handgrip strength scores than their counterparts. Logistic regression showed that better agility (for the forwards) and right handgrip strength scores (for the backs) were the only variables significantly associated with an increased likelihood of being recruited to the national team. In sum, these findings suggest that certain well-developed physical qualities, namely, agility for the forwards players and upper-body strength for the back players, partially explain the selection of U19 rugby players to their national team.